2000
DOI: 10.1038/sj.ejhg.5200442
|View full text |Cite
|
Sign up to set email alerts
|

Potential relationship between genotype and clinical outcome in propionic acidaemia patients

Abstract: Propionic acidaemia (PA) is an autosomal recessive disorder caused by mutations in either of the PCCA or PCCB genes which encode the α and subunits, respectively, of the mitochondrial enzyme propionyl-CoA carboxylase (PCC). In this work we have examined the biochemical findings and clinical outcome of 37 Spanish PA patients in relation to the mutations found in both PCCA and PCCB genes. We have detected 27 early-onset and 10 late-onset cases, showing remarkably similar biochemical features without relation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 21 publications
3
45
0
Order By: Relevance
“…Recently in one study, the correlation was described in PCCB homozygotes presenting with early onset form [20]. It is not surprising that the homozygotes with two mutations, T428I and 1527del3, in our study also presented with early onset and had null enzyme activities.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Recently in one study, the correlation was described in PCCB homozygotes presenting with early onset form [20]. It is not surprising that the homozygotes with two mutations, T428I and 1527del3, in our study also presented with early onset and had null enzyme activities.…”
Section: Discussionsupporting
confidence: 66%
“…In Perez-Cerda's study, four common mutations were found in 38/52 mutant chromosomes investigated, whereas the remainder of the alleles harbors 12 other different mutations [20]. The most frequent mutation in Spanish patients with PCCB gene defect is ins/del mutation, which replaces 14 bp in the coding sequence with 12 bp, unrelated to this region of the gene, followed by 1170insT, the second most common allele [21].…”
Section: Discussionmentioning
confidence: 95%
“…In virtually all reported cases of PA including atypical and mild ones, the diagnosis is supported by concurrent abnormal acylcarnitine profile and urine organic acids that identify the disease-specific 2-MCA and 3-OHP (AlDirbashi et al 2014;Weisfeld-Adams et al 2010;Pérez-Cerdá et al 2000). In this report, two individuals with compound heterozygous mutations in PCCA/PCCB present with significant C3 elevations in the absence of or only modest elevation in 2-MCA or 3-OHP, escaping the classic biochemical hallmarks for the PA diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…During acute intermittent illnesses, high-energy feeds without the precursor amino acids are required to prevent metabolic decompensation (Ogier de Baulny et al 2005;McDonald et al 2007;Deodato et al 2006). The prognosis of PA has been improving in the last years, with a larger amount of patients reaching adult life (Martín-Hernández et al 2009;Pérez-Cerdá et al 2000;Baumgartner et al 2007;Williams et al 2009). …”
Section: Introductionmentioning
confidence: 99%